Aplikasi Tanda Tangan Digital Pada Platform Android - Kristanto, Yoshua Indriasandy; Putra, Putu Bagus Adidyana Anugrah (Universitas Palangka Raya, 2022)
A signature or initial is a handwriting that is sometimes given a certain style of writing from a person's name or other identification mark. Basically, the signature has a function as written evidence that shows the fulfillment of the terms of the